Compensation and Bargaining with Entrpreneurship as the Outside Option - Erkki Koskela; Rune Stenbacka (Center for Economic Studies and ifo Institute (CESifo), 2000)
We analyze the impact of entrepreneurship as an outside option on compensation contracts between a principal and an agent with bargaining power. In the first stage the parties bargain over the base wage and the profit share. In the second stage the principal determines the capital investment and the agent decides on effort. It is shown that while negotiated base wage increases in the degree of the competitiveness in the market for outside equity funding, the profit share is invariant both to the imperfections prevailing in the equity market and to the relative bargaining power of the negotiating parties.
Keywords: 330; Wage bargaining; outside option; entrepreneurship